(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
The choice of the kindergarten and the group is decisive in a child’s life. It is difficult to decide whether a homogeneous or a heterogeneous group is better for children; and kindergarten teachers are also divided on which group they like to work in. Therefore, the study tries to find out what the kindergarten teachers think of a homogeneous and of a heterogeneous group. In our research, we used a questionnaire with kindergarten teachers; on the one hand, which groups were preferred by kindergarten teachers and on the other hand, which group was more difficult to work in. In the study, we also pointed out the opinion of kindergarten teachers: which group is better for children’s development.